The earliest Pleistocene archaeological sites in western Iberia: present evidences and research prospects - Oosterbeck, L. (2010)
Archaeological evidence for the earliest human presence in western Iberia is summarised and discussed. Western Iberia is geologically characterised by magmatic and metamorphic rocks (Hesperian Massif) but also by siliciclastic and carbonate Mesozoic and Cenozoic formations. The geological context affects the distribution of Pleistocene archaeological sites, as the most of the archaeological evidence known today is located in river terrace formations or in karst deposits. Very few sites have been fully investigated; the older ones are tentatively dated as middle/late Middle Pleistocene. Recent results have been obtained using an archaeological and geomorphological approach carried out in the Portuguese region of Alto Ribatejo. Dating of the lithic assemblages found in fluvial terraces or in cave deposits indicates that the first human presence in Portugal is not older than the OIS 8–9. However, it remains difficult to explain the long chronological gap between the archaeological evidences in western Iberia and the older sites in central and eastern Iberia, such as those in the Sierra de Atapuerca and Guadix Baxa areas.